PENGELOLAAN TAMAN TIRTO AGUNG SEBAGAI RUANG TERBUKA HIJAU DI KOTA SEMARANG - Dhamar Sosa Wibisono; Turtiantoro . (Journal of Politic and Government Studies, 2018)
Green Open Space is one of the urban elements that is very important to support the lives and activities of the population, because basically RTH is a natural element that plays a very important role in realizing an environmentally friendly city. The arrangement of the proportion of Green Open Space in urban areas is a minimum of 30% by the Government is a minimal measure to ensure the balance of urban development. This study aims to describe the management of Taman Tirto Agung and the obstacles experienced by the Housing and Settlement Area of Semarang City.The research method used is a descriptive qualitative approach with data collection techniques namely interviews, observation and documentation. Data sources used are primary data and secondary data. The informants in this study were the Head of the UPTD Landscaping Region VI of the Department of Housing and Settlements in Semarang City, the Head of the Landscaping Implementation Section of the Housing and Settlements Agency, visitors and traders of Taman Tirto Agung Banyumanik.The results showed that the management of Taman Tirto Agung Banyumanik was carried out according to the applicable procedures and rules with seven maintenance activities namely sweeping, watering plants, fertilizing, pruning, weeding and weeding, pest and disease control and planting, monitoring and evaluation activities and utilization of development Taman Tirto Agung Banyumanik. Taman Tirto Agung Banyumanik is also considered to be in accordance with its function as an active park. The constraints experienced by the Semarang City Housing and Settlement Office include less skilled workforce, weather factors and less responsible people by removing ornamental plants in the park, not throwing trash in their place and scribbling public facilities in the park location Tirto Agung. With the existence of this research, it is hoped that it can be used as input material in the Management of Green Open Space in the City of Semarang.The recommendation that can be given to the Semarang City Government is that by paying more attention to the workforce employed by the contractor, there needs to be a minimum competence possessed by the workforce employed so that the work results are in accordance with the desired standards. Providing guidance to the community, such as the routine distribution of seeds every month, socializes the importance of maintaining and maintaining green open spaces and educating the public about the importance of disposing of garbage in its place.Keywords: green open space; management; City Park